2010
DOI: 10.3389/fncir.2010.00016
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal excitability of oblique dendrites implicated in early Alzheimer's: a computational study

Abstract: The integrative properties of cortical pyramidal dendrites are essential to the neural basis of cognitive function, but the impact of amyloid beta protein (aβ) on these properties in early Alzheimer's is poorly understood. In animal models, electrophysiological studies of proximal dendrites have shown that aβ induces hyperexcitability by blocking A-type K+ currents (IA), disrupting signal integration. The present study uses a computational approach to analyze the hyperexcitability induced in distal dendrites b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 57 publications
3
40
0
Order By: Relevance
“…In our previous work, we have evaluated various ionic channels in the hippocampal pyramidal neurons, which have been reported to be affected by Aβ. Specifically, changes in I Ca , I A , I K and I CT have been evaluated and we found that only Aβ-blocked I A has induced a significant theta band power change (Zou et al 2011), probably due to the increased pyramidal neuronal excitability (Morse et al 2010). In this paper, a wider range of model parameters of I A will be explored and the corresponding theta band power changes will be evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…In our previous work, we have evaluated various ionic channels in the hippocampal pyramidal neurons, which have been reported to be affected by Aβ. Specifically, changes in I Ca , I A , I K and I CT have been evaluated and we found that only Aβ-blocked I A has induced a significant theta band power change (Zou et al 2011), probably due to the increased pyramidal neuronal excitability (Morse et al 2010). In this paper, a wider range of model parameters of I A will be explored and the corresponding theta band power changes will be evaluated.…”
Section: Introductionmentioning
confidence: 98%
“…Deterministic approximations allow examining reaction-diffusion dynamics in whole dendrites (e.g., Calcium Waves in Neymotin et al 2015; ModelDB 168874). Single cell models allow investigating the effects of modulators on the electrophysiology of individual neurons (e.g., Morse et al 2010; ModelDB 87284 explores the early effects of amyloid beta on a CA1 pyramidal neuron). Another class of single cell models focuses on gene expression (e.g., circadian rhythms in the suprachiasmatic nucleus of the brain, Kim and Forger 2012; ModelDB 145801).…”
Section: Modeldb and The Future Of Neurosciencementioning
confidence: 99%
“…A typical morphologically detailed single neuron model (modeldb.yale.edu/87284; Morse et al 2010). (A) A traced neuron (NeuroMorpho.Org c91662) is discretized into many (here 974) compartments.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations